Effect of Soft Tissue Thickness on the Morphology of Lip in Orthodontic Treatment/Efecto del Grosor del Tejido Blando en la Morfologia del Labio en el Tratamiento de Ortodoncia - Guan, Yu-Xin; Xin, Li; Tian, Peng-Fei; Kyung, Hee-Moon; Kwon, Tae-Geon; Bing, Li; Wu, Xiu-Ping (International journal of morphology, 2019)
The aim of this study was to evaluate the effect of soft tissue thickness of upper lip on lip retraction in orthodontical-treated females and identify the ratio of maxillary incisor retraction to upper lip retraction. Pre- and post-treatment lateral cephalograms of 100 adults were examined to measure the lip thickness in upper lip and establish the classification standard. All subjects were treated with 4 first premolar extractions followed by upper central incisors retraction. Pre- and post-treatment lateral cephalograms of 19 patients were reviewed to determine the changes of the upper lip and incisor positions through landmarks displacement. An independent-samples t test and one-way analysis of variance were performed. The correlations between maxillary incisor retraction and upper lip retraction were explored by the Pearson correlation method. P-values<0.05 were considered statistically significant. The lip thickness of adult male patients was greater than that of adult female patients. The average ratio of maxillary incisor retraction to upper lip repositioning was 1.6:1,1.9:1 and 2.2:1 in the thin lips group, normal lips group and thick lips group, respectively. Gender differences exist in the thickness of upper lip. Horizontal changes of the maxillary incisor showed a significant correlation to horizontal changes of the upper lip (P<0.001).There were negative correlations between the thickness of upper lip and the ratio between change in maxillary incisor protrusion and change in upper lip protrusion. KEY WORDS: Morphological characteristics; Malocclusion; Incisor retraction; Cephalometric measurements; Soft tissue profile.